1951
DOI: 10.1017/s002202990000594x
|View full text |Cite
|
Sign up to set email alerts
|

435. Keeping quality and raw-milk grading: II. The effect of storage on the results of keeping quality and dye tests

Abstract: 1. The experiments described in this part of the report were designed to obtain information about the effect of time and temperature of pre-test storage on test results and, in particular, about the possibility of a practical method of compensating test results to eliminate or minimize their dependence on the time and temperature of pre-test storage.2. Four separate experiments were planned and carried out in three widely separated areas in England and Wales. Samples of morning milk, brought to the laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1951
1951
1968
1968

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Correction of the keeping quality times for the portions held for 23 hr. a t 14" t312 for the equivalent periods of storage was made using the formula R(t)= of milk a t different temperatures (Eddison et al 1951). From this, calculation shows that each hour of storage a t 14"(t) is equivalent to 0.46 hr.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Correction of the keeping quality times for the portions held for 23 hr. a t 14" t312 for the equivalent periods of storage was made using the formula R(t)= of milk a t different temperatures (Eddison et al 1951). From this, calculation shows that each hour of storage a t 14"(t) is equivalent to 0.46 hr.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Two-oz portions of milk were placed in a low temperature water bath a t 4 pm on the day of sampling and maintained at 22"&0*5" until the time of testing the following day. This was determined by the mean atmospheric shade temperature between 9 am and 4 pm on the day of sampling, according t o the scale suggested by Eddison et al (1951). Five ml of the sample were poured into a 6 x 9 in.…”
Section: Bacteriological Testsmentioning
confidence: 99%
“…The authors concluded, therefore, that temperature compensat,ioii may be applied to keeping quality results, or, in other words, that the results to be expected after storage at one temperature may be calculated from the results obtained after storage at any other temperature, the error being relatively small. Further data have been given by Rowlands & Hosking (1951).…”
Section: (F) Bacteriological Testing Aspectsmentioning
confidence: 99%